A comparative cross-reactivity and paraspecific neutralization study on Hypnale hypnale, Echis carinatus, and Daboia russelii monovalent and therapeutic polyvalent anti-venoms. - Vaddaragudisalu D Sandesha; Bhaskar Darshan; Chandrashekar Tejas; Kesturu S Girish; Kemparaju Kempaiah (Public Library of Science (PLoS), 2022)
Envenoming by the hump-nosed pit viper (Hypnale hypnale) raises concern as it inflicts significant debilitation and death in the Western Ghats of India and in the adjacent island nation of Sri Lanka. In India, its medical significance was realized only during 2007 due to its misidentification as Echis carinatus and sometimes as Daboia russelii. Of late, several case reports have underlined the ineptness of the existing polyvalent anti-venom therapy against H. hypnale envenoming. Currently, H. hypnale bite has remained dreadful in India due to the lack of neutralizing anti-venom therapy. Hence, this study was undertaken to establish a systematic comparative, biochemical, pathological, and immunological properties of Sri Lankan H. hypnale venom alongside Indian E. carinatus, and D. russelii venoms. All three venoms differed markedly in the extent of biochemical activities including proteolytic, deoxyribonuclease, L-amino acid oxidase, 5'-nucleotidase, hyaluronidase, and indirect hemolytic activities. The venoms also differed markedly in their pathological properties such as edema, hemorrhage, myotoxic, cardiotoxic, and coagulant activities. The venoms showed stark differences in their protein banding pattern. Strikingly, the affinity-purified rabbit monovalent anti-venoms prepared against H. hypnale, E. carinatus, and D. russelii venoms readily reacted and neutralized the biochemical and pathological properties of their respective venoms, but they insignificantly cross-reacted with, and thus failed to show paraspecific neutralization of any of the effects of the other two venoms, demonstrating the large degree of variations between these venoms. Further, the Indian therapeutic polyvalent anti-venoms from VINS Bioproducts, and Bharath Serums and Vaccines failed to protect H. hypnale venom-induced lethal effects in mice.